MAKING SENSE OUT OF U.S. TRADE POLICY OR HIGH-STAKES POKER GAME? - hunter, richard j (Archives of Business Research, 2019)
This paper is a study of the genesis and function of the Office of United States Trade Representative. It describes the National Trade Estimate on Foreign Trade Barriers and the Special 301 Report which delineates countries placed on the Priority Watch List and Watch List for alleged violations relating to U.S. intellectual property rights. The paper also provides a discussion of Notorious Markets, both online and physical, and offers suggestions for the implementation of enforcement strategies to combat piracy and other forms of theft of U.S. intellectual property.